Diagnóstico socioambiental da contaminação por hidrocarbonetos de petróleo em aquífero na cidade de João Pessoa-PB - Costa, Cristian José Simões (2023)
The general objective of the exploratory qualitative and quantitative research was to carry out a diagnosis of groundwater regarding the presence of petroleum hydrocarbons, called BTEX, HPA and TPH present in fossil fuels, arising from the resale activity of gas stations in the city of João Pessoa - PB. Using interdisciplinarity, several control bodies were consulted to survey the profile of gas stations based on the number of stations, infractions, licenses and tanking diagnosis. The identification and mapping of the wells was carried out from the databases of the Groundwater Information System, belonging to the Mineral Resources Research Company – CPRM; of the Water Management Executive Agency; of the Paraíba Water and Sewage Company and visits to identify wells not registered in the official bodies. In another stage, a risk assessment was carried out with all the gas stations in the city using previously selected criteria and which follow an order of greater relevance for the investigation of environmental liabilities. It was considered, considering in this assessment the proximity of the underground well in relation to the underground fuel tanks, average well depth, vulnerability of the aquifers, the classification considering the surroundings of the enterprise, the elevation profile, and the history of accidents at the gas stations. The methodology used, indicated by the Contaminated Areas Management Manual (ACs), established by CETESB (2001), aims to define the existence and location of the contaminated areas under investigation, optimizing technical and economic resources. Based on this information, 38 gas stations from the four zones of the city were selected with averages that showed scenarios conducive to contamination, identified in the risk assessment. Over a two-year period, around 180 visits were made to gas stations and 114 samples were collected from the four zones of the city, 38 for BTEX analysis, 38 for PAH analysis and 38 for TPH analysis. The results of the confirmatory evaluation show that there is no contamination by BTEX in the four zones of the city of João Pessoa and that there is also no contamination caused by PAH and TPH in groundwater in the North, South and West zones. The only evidence of contamination was in the East zone, with the presence of PAH and TPH. For PAH, Naphthalene was found at a concentration above CONAMA Resolution 420, of 144.87 μg.L and Ethylbenzene with 44.81 μg.L, which was below all legislation dealing with this contaminant. TPH was found at two different points and in much higher concentrations (1485.1 and 2379.8 μg.L) than those established by CETESB, 2014, which determines a maximum value of 600 μg.L. The maps produced with the survey data make it possible to identify the city regions with the highest risk assessment averages and the contaminated areas.